Gambaran Kualitas Hidup Pekerja Pra Lanjut Usia (45-56 Tahun) Dengan Sindrom Metabolik Di PT. X Tahun 2020 - Fierdania Yusvita; Putri Handayani; Nadya Shinta Nandra (Journal of Natural Sciences, 2021)
Quality of life can be determined by the individual's perception of his current life, including his health condition. Among occupational diseases, degenerative diseases are the first cause of death, and metabolic syndrome is one of them. This study aims to describe the quality of life of pre-elderly workers (45-56 years) with the risk of metabolic syndrome (obesity, hypertension, hypercholesterolemia and hyperglycemia) at PT. X. The research was conducted with a qualitative descriptive method. Data was collected by interview method and the results of medical check-up documents. The results showed that the respondents rated their quality of life quite well. They judged that his current physical condition was quite good. Respondents do not know that their current health condition can trigger degenerative diseases in the future if sedentary behavior is still ignored. Five of the seven respondents still do not exercise regularly and three of the seven respondents are active smokers with cigarette consumption of 3-20 cigarettes/day. The seven respondents did not pay enough attention to their food intake. Psychologically, respondents perceive their mental condition is very good, they perceive the work environment as a very comfortable place to build social relationships. More metabolic syndrome related support programs at PT X need to be offered to increase workers' awareness of their health status.